Assessment Of Soft Tissue Facial Profile, Nasal Airway Morphology And Dental Arch Features In Adult Malay Obstructive Sleep Apnea Patients Using Geometric Morphometric Analysis. - Saeed Banabilh, Saeed Mohammed (2008)

(untitled)
Masalah tidur apnea obstruktif (OSA) telah dikenal pasti sebagai satu masalah yang memberi impak kepada masyarakat setanding dengan masalah merokok.